Decision-Making in Ambiguous Situations: The Impact of Neosexism and Gendered Settings - Grawitch, Matthew; Lavigne, Kristi; Saffaf, Falak (Journal of Open Inquiry in the Behavioral Sciences, 2025)
This study examined how people judge whether an interaction is sexist when the situation is ambiguous. We tested how judgments were influenced by (a) sex composition of the interaction (e.g., male-female, female-female), (b) the setting of the interaction (banking, a traditionally male-typed context vs. daycare, a traditionally female-typed context), and (c) individual attitudes about sexism. Across two scenarios, people rated the behavior as more sexist when a male addressed a female in the banking context. This effect was absent in the daycare context. People who showed more sensitivity to potential sexism were more likely to rate behavior as sexist across both contexts, and this affected how favorable they found the interaction and what advice they gave in response. These findings suggest that both individual beliefs and situational context shape how people interpret potentially biased behavior.